Low complexity codebook search method in massive MIMO system - Jianfei LIU; Liping HE; Ying TAO; Di LIU; Xiangye ZENG; Mengjun WANG (Tongxin xuebao)
In Massive MIMO systems for 5G networks,precoding technology is one of the key technologies.Aiming at user side codebook search method of the discrete Fourier transform (DFT) rotation codebook,a low complexity search algorithm was proposed.In this algorithm,all horizontal and vertical codebooks were grouped separately according to the characteristics that the precoding vectors with the same column of DFT rotation codebooks had the smallest chordal distance and the smaller chordal distance have the stronger correlation,and then the optimal horizontal and vertical codewords with maximum channel gain were obtained to form 3D precoding code-books.The simulation results indicate that the searching complexity of the proposed method is significantly reduced under conditions of insuring the system performance,moreover,this advantage becomes greater with the number of antennas increasing.